KARAKTERISTIK PENDERITA STROKE HEMORAGIK RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH TAHUN 2015-2016 - Ronny Mardianto Tondang; Fazidah A Siregar; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Stroke occupies the third position in the order of causes of death, after heart disease and cancer. Stroke can be classified into two types, namely hemorrhagic stroke and nonhemoragik stroke (ischemic).The incidence of hemorrhagic stroke between 15% - 30% and non hemorrhagic stroke between 70% - 85%. Proportion of hemorrhagic stroke patients in Santa Elisabeth Hospital Medan in 2015-2016 based on stroke of 23,37%. To identify the characteristics of hemorrhagic stroke patients in the Hospital Santa Elisabeth Medan, conducted descriptive research with case series design. The population of this study were all hemorrhagic stroke patients with the same sample size as the population (total sampling). In Santa Elisabeth Hospital Medan was found 165 stroke haemorragic patients in 2015-2016. The highest sociodemographic proportions: age group 55-64 years with male gender 20.6%, Batak tribe 86.7%, Protestant Christianity 71.5%, 95.2% married, civil servant / TNI / POLRI / pensioner 32 , 1%, and outside of Medan 58.8%. Hypertensive factors 66.1%, intracerebral hemorrhage 66.7%, hexiparesis dextra 47.9%, cerebral hemisphere 41.8%, conservative action 82.4%, average treatment duration 10.87 days (11 days) own cost 61,2%, go home with 57,6% street treatment, bleeding location and highest position of paralysis in cerebral hemisphere with paralysis location at dextra hemiparesis equal to 49,3%. Case fatality rate based on the highest age is>60 years 27,66%, male 25,25%, brain stem 80,0%, operative action 34,48%. For inpatients who have a history of hypertension to perform routine control and apply a healthy lifestyle to prevent stroke and subsequent stroke. For hospitals it is expected to complete the recording of hemorrhagic stroke patient data on status cards especially those related to education, and handling stroke. Keywords: Hemorrhagic Stroke, Patient Characteristics